1997
DOI: 10.1007/bf01628133
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical variants of the profunda femoris artery: An angiographic study

Abstract: The bifurcation of the common femoral artery (CFA) into superficial and profunda femoris arteries (PFA) and the branching pattern of the PFA are subject to considerable normal anatomical variation. These variation patterns were assessed on normal lower limb angiograms of 94 adult patients. The main pattern (in 81% of patients) consisted of both medial and lateral circumflex arteries arising directly from a PFA situated lateral or posterolateral to the femoral artery. Previous studies of arterial variations in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
3

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(19 citation statements)
references
References 15 publications
0
16
0
3
Order By: Relevance
“…While all studies except for two used cadaveric data (Massoud & Fletcher, 1997; Gościcka, Gielecki & Zietek, 1990), the imaging subgroup results were not significantly different from the overall analysis. As such, we attribute the high heterogeneity to the naturally high variability of the MCFA.…”
Section: Discussionmentioning
confidence: 84%
See 3 more Smart Citations
“…While all studies except for two used cadaveric data (Massoud & Fletcher, 1997; Gościcka, Gielecki & Zietek, 1990), the imaging subgroup results were not significantly different from the overall analysis. As such, we attribute the high heterogeneity to the naturally high variability of the MCFA.…”
Section: Discussionmentioning
confidence: 84%
“…The studies spanned from 1934 to 2015 and demonstrated a wide geographical distribution with studies hailing from North America, Europe, Asia and Africa. The type of study included in the meta-analysis was predominantly cadaveric, except for studies by Massoud & Fletcher (1997) and Gościcka, Gielecki & Zietek (1990) who used digital subtraction transfemoral aortogram and radiograms, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…U našem istraživanju analizirane su razlike mesta nastanka ACFL u odnosu na stranu tela i pol i utvrđeno je da ne postoji statistički značajna razlika između navedenih parametara, što odgovara podacima objavljenim u literaturi [20,28,29].…”
Section: Diskusijaunclassified